2021
DOI: 10.2298/gensr2101419a
|View full text |Cite
|
Sign up to set email alerts
|

Genetic response of growth phases for abiotic environmental stress tolerance in cereal crop plants

Abstract: The yield potential and quality of main cereals crop plants including maize, wheat, rice and barley have improved through breeding and introduction of transgenic crop plants from last three decades. There has been intensive research for the improvement of resistance against biotic and abiotic environmental conditions to safe the potential of cereal crop plants. Among abiotic stresses drought and heat are two most important abiotic factors which caused major loss in yield and quality of crop p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 271 publications
(357 reference statements)
0
7
0
Order By: Relevance
“…The expression of LXC003712 and the rest of the genes involved in carbon fixation by photosynthesis were also upregulated in strain X5 of 60‰ ( Figure 10 ). According to previous reports, the expression of the genes involved in photosynthetic carbon fixation are also upregulated in higher plants exposed to abiotic stresses (e.g., high salt, high osmotic pressure) that affect photosynthesis [ 47 , 48 ]. This suggested that the red alga G. lemaneiformis may have a mode of regulation that is similar to that of higher plants in response to similar stresses.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of LXC003712 and the rest of the genes involved in carbon fixation by photosynthesis were also upregulated in strain X5 of 60‰ ( Figure 10 ). According to previous reports, the expression of the genes involved in photosynthetic carbon fixation are also upregulated in higher plants exposed to abiotic stresses (e.g., high salt, high osmotic pressure) that affect photosynthesis [ 47 , 48 ]. This suggested that the red alga G. lemaneiformis may have a mode of regulation that is similar to that of higher plants in response to similar stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Plant breeding programs depend on having a lot of different genetic material to choose from. Finding and using different strains to hybridize with elite cultivars is important for increasing the genetic base of core breeding materials (Aaliya et al, 2016;Ali and Malik, 2021;Juma et al, 2021;Mazhar et al, 2020;Mustafa et al, 2018;Naseem et al, 2020). Much research has been done on the genetic diversity of breeding materials for different crops.…”
Section: Assessing Genetic Variation and Parental Selectionmentioning
confidence: 99%
“…LTS results in short statured spikes, reduced number of spikelets, pollination failure, poor grain filling, and inadequate seed setting (Liu et al, 2019a). Wheat plant's upper spikelets turns pale yellow or partially dies on exposure to LTS at booting stage (Kodra et al, 2011;Sanghera et al, 2011) abnormal pollen and ovule development, leading to pollen inactivation, floret sterility, and eventually cause abortion (Ali and Malik, 2021). Denatured spikelets, reduced assimilate transport, decreased dry matter accumulation, and poor grain yield are all consequences of LTS (Whaley et al, 2004).…”
Section: Morpho-physiological Impairments and Molecular Expressions A...mentioning
confidence: 99%